Aquedücte: A Data Integration Service for Smart Cities - Silva, Jorge; Almeida, João Gabriel; Batista, Thais; Cavalcante, Everton (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2021: Proceedings of the 27th Brazilian Symposium on Multimedia and the Web, 2021)
In smart city scenarios, a plethora of data is generated from multiple, decentralized sources, e.g., systems, applications, citizen devices, sensors, etc. However, these data may be not readily available for use due to the high heterogeneity of types, formats, and protocols, thereby giving rise to vertical silos that hamper sharing, integrating, and exploiting these data. This paper introduces Aquedücte, a data integration service for smart cities. Aquedücte offers functionalities for (i) handling data from heterogeneous sources such as files, Web services, systems, etc., (ii) converting these data to a common protocol, and (iii) making them further available to platforms aimed to support the development of smart city applications.